2004
DOI: 10.1557/jmr.2004.0282
|View full text |Cite
|
Sign up to set email alerts
|

High Curie temperature perovskite BiInO3–PbTiO3 ceramics

Abstract: The extent of BiInO3 substitution in the perovskite system xBiInO3–(1 - x)PbTiO3 and the corresponding raise in the Curie temperature were investigated using thermal analysis, dielectric measurements, x-ray diffraction, and electron microscopy. Maximum tetragonal perovskite distortion (c/a = 1.082) was obtained for x = 0.20, with a corresponding Curie temperature of 582 °C. Phase-pure tetragonal perovskite was obtained for x ⩽ 0.25. Compound formation after calcining mixed oxide powders resulted in agglomerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…Its solid solutions with PbTiO 3 , for example, are extensively used because they can preserve the high piezoelectric activity up to relatively high temperature and reduce the amount of lead. [1][2][3][4][5][6][7] First-principles calculations of piezoelectric alloys xBiScO 3 -͑1−x͒PbTiO 3 ͑Ref. 8͒ suggested that the large structural distortions and polarizations, at the morphotropic phase boundary, come from the hybridization between Bi/ Pb 6p and O 2p orbitals, a mechanism that is enhanced upon the substitution of Pb by Bi.…”
Section: Introductionmentioning
confidence: 99%
“…Its solid solutions with PbTiO 3 , for example, are extensively used because they can preserve the high piezoelectric activity up to relatively high temperature and reduce the amount of lead. [1][2][3][4][5][6][7] First-principles calculations of piezoelectric alloys xBiScO 3 -͑1−x͒PbTiO 3 ͑Ref. 8͒ suggested that the large structural distortions and polarizations, at the morphotropic phase boundary, come from the hybridization between Bi/ Pb 6p and O 2p orbitals, a mechanism that is enhanced upon the substitution of Pb by Bi.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent performance of Bi-perovskites in solid solution with Pb-based perovskites were predicted and reported [2,3]. For example, PbTiO 3 -Bi(Zn 1/2 Ti 1/2 )O 3 [4][5][6], PbTiO 3 -Bi(Mg 1/2 Ti 1/2 )O 3 [7,8], PbTiO 3 -Bi(Ni 1/2 Ti 1/2 )O 3 [9], PbTiO 3 -BiScO 3 [10,11], and PbTiO 3 -BiInO 3 [12,13] compounds have been reported to exhibit a high Curie temperature (T C ), which is a great advantage for high temperature applications. These Biperovskites were also investigated in solid solutions with Pb-free ferroelectric materials such as BaTiO 3 .…”
Section: Introductionmentioning
confidence: 94%
“…In order to confirm the effect of the BF, other Bi-perovskite such as BiInO3 (BI) 11) and BiScO3 (BS) 9),10) were also added to the LF4.…”
Section: )8)mentioning
confidence: 99%